INCREASING STUDENTS' WRITING SKILL USING LITERATURE: CLASSROOM ACTION RESEARCH AT MAN 1 PROBOLINGGO - Susmiati, Endang; Tirmidi, Tirmidi; Kaharudin, Utsman (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This classroom action research aims to improve students' writing skills through the implementation of literature-based learning, specifically poetry, integrated into the learning module in English lessons at MAN 1 Probolinggo. The research was conducted in two cycles covering the stages of planning, implementation, observation, and reflection, with 11th-grade students as the subjects. Data were collected through observation, interviews, and document analysis, then analyzed qualitatively and quantitatively. The results of the study showed a significant improvement in students' writing skills, in terms of creativity, word choice, and sentence structure, as indicated by an increase in the average writing score from the pre-test to the post-test. Poetry-based learning also created a reflective and inspiring classroom atmosphere, helping students see writing not only as language practice, but as a means of meaningful self-expression. Thus, this learning strategy proved effective in improving students' writing competence and overall learning motivation.